2019
DOI: 10.1002/2211-5463.12741
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA expression profiles in extracellular vesicles from the plasma of patients with pancreatic ductal adenocarcinoma

Abstract: Tumor‐derived extracellular vesicles (EVs) and their contents are involved in the development of human malignancies. Circular RNAs (circRNAs), enriched in EVs, can regulate diverse cellular processes by acting as microRNA (miRNA) sponges or through other mechanisms. In the present study, we explored the potential roles of circRNAs in EVs in the development of pancreatic ductal adenocarcinoma (PDAC). First, plasma was obtained from patients with PDAC (n = 8) and healthy volunteers (n = 8), and EVs were isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Additional microarray data revealed that there were 115 upregulated and 141 downregulated circRNAs in PDACs (75). Another study uncovered that 453 circRNAs were differentially expressed and were significantly different in extracellular vesicles isolated from the plasma of 8 PDAC patients or healthy controls (76). It has been suggested that aberrant expression of circRNAs in PDAC are related to proliferation and development.…”
Section: Circrnas In Pdacmentioning
confidence: 99%
“…Additional microarray data revealed that there were 115 upregulated and 141 downregulated circRNAs in PDACs (75). Another study uncovered that 453 circRNAs were differentially expressed and were significantly different in extracellular vesicles isolated from the plasma of 8 PDAC patients or healthy controls (76). It has been suggested that aberrant expression of circRNAs in PDAC are related to proliferation and development.…”
Section: Circrnas In Pdacmentioning
confidence: 99%
“…Beyond their localization in the nucleus and/or cytoplasm, are circRNAs distributed in other locales? Recent reports have identified circRNAs in extracellular vesicles, including those derived from tumor cells (Hon, Ab‐Mutalib, Abdullah, Jamal, & Abu, 2019; Lasda & Parker, 2016; Q. Li, Geng, et al, 2019; Y. Li, Zhao, et al, 2019; Shi et al, 2020). Are they only found in membrane‐enclosed structures or also in free solution?…”
Section: Discussion and Closing Remarksmentioning
confidence: 99%
“…A total of 453 differentially expressed circRNAs, consisting of 274 upregulated and 179 downregulated circRNAs, were discovered in exosomes from the plasma of patients with pancreatic ductal adenocarcinoma (PDAC) relative to healthy volunteers. 159 It was proposed that these exosomal circRNAs might regulate PDAC pathogenesis by targeting miRNAs in recipient cells. Recently, 182 exosomal circRNAs were reported to be differentially expressed in the plasma from LUAD patients compared with healthy controls.…”
Section: Origin Of Exosomal Circrnasmentioning
confidence: 99%